Un enseignement purement distanciel de la traduction grâce à une plateforme collaborative est-il possible ? Leçons d’une pandémie - Lacour, Philippe; Elbaz, Pascale; Jamborova Lemay, Diana; Roesler, Layla; Postlewate, Laurie (2023)
This article examines the rapid and radical adaptations to total distance learning that the COVID-19 pandemic required of teachers using TraduXio, a multilingual digital translation platform for collaborative translation work (https://traduxio.org). The teachers discuss the changes that the sudden transition brought to their classroom work, which included adjusting activities to suit the evolving needs of the learners and the varying reactions of the students themselves; they conclude by providing a brief assessment of the advantages and disadvantages of the 100% distance learning/teaching situation. Three main benefits of the switch to distance learning of translation are addressed: 1) making learners aware of the importance of individual interpretation in translation, 2) developing their sensitivity to consistency in translation choices across a group of translators (terminology, tense, tone), and 3) focusing their attention on the importance of discussion in the translation process.
Keywords: translation; collaboration; distance teaching; pandemic